2016
DOI: 10.46743/1540-580x/2016.1580
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Interprofessional Education Event for Graduate Health Professional Students

Abstract: Purpose: The purpose of this study was to investigate the impact of a single, optional, half-day, interprofessional education (IPE) event for a myriad of graduate-level health professional students (n=44) at a university in Illinois, USA. Methods: The researchers in this study examined students’ performance on two out of six of the domains on the Interprofessiomnal Collaborator Assessment Rubric (ICAR): Roles and Responsibilities and Communication Strategies. This study also investigated quantitative and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Besides that, this IPE activity could have encouraged better understanding of professional roles in patient care as well as generate constructive mutual attitudes. The IPE activity was as effective as others done physically that other studies have reported on [32]. One of the reasons for the successful outcome might be that the patient case was designed in such a way that both disciplines had to use their knowledge and communication to solve it.…”
Section: Discussionmentioning
confidence: 81%
“…Besides that, this IPE activity could have encouraged better understanding of professional roles in patient care as well as generate constructive mutual attitudes. The IPE activity was as effective as others done physically that other studies have reported on [32]. One of the reasons for the successful outcome might be that the patient case was designed in such a way that both disciplines had to use their knowledge and communication to solve it.…”
Section: Discussionmentioning
confidence: 81%